HUBUNGAN TINGKAT PENGETAHUAN DENGAN SIKAP ORANG TUA TENTANG TOILET TRAINING PADA ANAK USIA TODDLER (1-3 TAHUN) (Di PAUD PELITA ILMU Kelurahan Mrican Kecamatan Mojoroto) - erna susilowati; Riris Rinjarti Pratiwi (JURNAL KEBIDANAN, 2016)
Less knowledge and attitudes of parents about toilet training cause parents give negative attitudes in children. Nurses role as educators is to facilitate parents to get information about the proper method or manner do toilet training in health education. This research aims to determine the relationship is there a knowledge with the attitudes of parents about toilet training. This research is a correlation with the population of all parents who have children aged 1-3 years in getting the samples in this research conducted with 23 respondents Total Sampling. The variable in this research is the dependent variable level of knowledge about toilet training and independent variable attitudes of parents on toilet training with the Spearman Rank Test statistic obtained significant results with values of 0.05 in getting P value 0.015 The research results get H0 rejected H1 received by this there is a correlation between the level of knowledge with the attitudes of parents about toilet training supported with the results of the research (91.3%) had good knowledge level of (65.2%) largely supportive attitude about toilet training. The conclusion from this research that there is a relationship between the level of knowledge with the attitude of a good parent as well as the support of the toilet training of children. The high the level of knowledge, the attitude is also getting better. Suggestion in the hope that nurses can implement awareness toilet training of children by parents. , ,